PENGARUH PEMBERIAN DISCHARGE PLANNING TERHADAP KEMAMPUAN KELUARGA DALAM PERAWATAN PASCA STROKE DI RUMAH TAHUN 2019 - Yaslina Yaslina; Maidaliza Maidaliza; Itra Hayati (LPPM UNIVERSITAS PERINTIS INDONESIA, 2019)
Post-stroke patients admitted to hospital in fact did not get a good discharge planning for the family, therefore this study aims to examine the effect of giving discharge discharges on the ability of families in post-stroke care at home. The method of this research is the design of correlation with the population whose sample is the family of patients after stroke. The research was carried out on January 2, 2019 until February 10, 2019. The results showed post-stroke family ability at home before discharge planning with Mean = 12.2 and with Standard Deviation 2.1 and results of post-stroke family abilities at home after discharge planning with Mean = 21.3 and with Standard Deviation 2.9. Statistical test results obtained p value 0,000. It was concluded that this study had the effect of discharge planning on the ability of families in post-stroke care at home. And it was suggested to hospital staff to provide discharge planning about to treat post-stroke at home such as diet, exercise and ADL including: to the toilet, eat, dress, bathe, and move places.